Avaliação da relação entre a resistência ao cisalhamento e a resistência à compressão paralela às fibras de madeiras do grupo das folhosas - Couto, Natalia Garcia (2019)
Wood presents several advantages when compared with other materials employed in the civil construction sector. In Brazil, the standard ABNT NBR 7190: 1997 establishes test methods to determine physical and mechanical properties. However, tests demands procedures on specialized and high-cost laboratories. The Brazilian code displays different values for relations between shear strength and compression strength parallel to the fibers. This study aimed to investigate, considering the results of the compressive strength and shear strength parallel to the fibers tests, the relationship between these properties obtained with the statistical assistance of least square method and considering ten hardwood wood species. The results were compared with the relationship values disposed on the Brazilian Code ABNT NBR 7190:1997, being the greatest coefficient found 86,4% higher than the coefficient presented by the Brazilian code, considering the set of all species. Regarding the variation of the relationship between the investigated properties, considering the different classes of wood resistance, no study was identified that decreases in the values of the greatest coefficients as the classes increases, a situation that ABNT NBR 7190: 1997 exposes in its text, thus presenting another divergent result.